Hospital Medicine and Perioperative Care: A Framework for High‐Quality, High‐Value Collaborative Care. Issue 4 (1st April 2017) - Thompson, Rachel E.; Pfeifer, Kurt; Grant, Paul J.; Taylor, Cornelia; Slawski, Barbara; Whinney, Christopher; Wellikson, Laurence; Jaffer, Amir K.
Abstract : BACKGROUND: Hospitalists have long been involved in optimizing perioperative care for medically complex patients. In 2015, the Society of Hospital Medicine organized the Perioperative Care Work Group to summarize this experience and to develop a framework for providing optimal perioperative care. METHODS: The work group, which consisted of perioperative care experts from institutions throughout the United States, reviewed current hospitalist‐based perioperative care programs, compiled key issues in each perioperative phase, and developed a framework to highlight essential elements to be considered. The framework was reviewed and approved by the board of the Society of Hospital Medicine. RESULTS: The Perioperative Care Matrix for Inpatient Surgeries was developed. This matrix characterizes perioperative phases, coordination, and metrics of success. Additionally, concerns and potential risks were tabulated. Key questions regarding program effectiveness were drafted, and examples of models of care were provided. CONCLUSIONS: The Perioperative Care Matrix for Inpatient Surgeries provides an essential collaborative framework hospitalists can use to develop and continually improve perioperative care programs.